PENAMBAHAN KINESIOLOGY TAPE PADA PELATIHAN CLOSED KINETIC CHAIN (CKC) DAN STRETCHING LEBIH BAIK DALAM MENURUNKAN EXCESSIVE Q-ANGLE PADA WANITA - Surya Adhitya, I Putu Gde; Adiputra, I Nyoman; Indra Lesmana, Syahmirza; Putu Sutjana, I Dewa; Muliarta, I Made; Imron, M. Ali (Sport and Fitness Journal, 2017)
Background: Q-angle is the angle between the quadriceps and patellar tendon and showing the angle of the quadriceps muscle tension. Pelvic widening in women does not occur in men who lead the Q-angle in women begins to enlarge during adolescence than men. Purpose: The purpose of this study was to compare the addition of kinesiology tape on CKC training and stretching without additional kinesiology tape on CKC training and stretching in women. Methods: This research was a randomized experimental design with pre-test and post-test group design. The sample contain by 24 people divided into two groups of 12 people each. Treatment group with the addition of kinesiology tape on CKC training and stretching, while the control group only CKC training and stretching. This research was conducted for 8 weeks, 2 times in a week. The data collected by the Q-angle measured using a goniometer at the time before and after treatment. Result: The results of data analysis using the Wilcoxon Signed Ranks Test, Q-angle was obtained with p = 0.002 for the different treatment groups with an average of 12.25 and in control group acquired Q-angle, with p = 0.002 with 6.416 average difference, and different 47.59% with treatment group. Mann-Whitney test results the average of difference of decreasing of treatment group is 18.5 and the average of difference of control group is 6.5 different 64.86% with treatment group, showed that there were significant differences in the decrease in Q-angle between the two groups with the result p = 0.001 (p <0.05). Conclusion: Conclusions of research are: the addition of kinesiology tape on the training of Closed Kinetic Chain (CKC) and stretching better in reducing excessive Q-angle in women. Suggestion: For the next research suggest to add dependent variables as: muscle strength, functional and speed of muscle contraction of Vastus Medial Oblique (VMO), individual addressing treatment, and use x-ray as measurement tool.